GORONTALO AND JAVANESE ETHNICITY: AN OVERVIEW OF INTERCULTURAL COMMUNICATION - Taufik R Talalu; Wahidah Suryani; Momy A Hunowu; Sri Dani Hijrana (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2022)
This study describes the effectiveness of intercultural communication among the people of Suka Mulya Village, which is home to the two most populous ethnic groups, the Gorontalo and the Javanese. This study employs a qualitative research method. Data successfully collected from primary and secondary sources via interviews and observation was analyzed through data reduction, data presentation, and concluding/data verification. The study's findings revealed intercultural communication between Gorontalo and Javanese ethnics in Suka Mulya Village, as evidenced by seven indicators: mutual respect, cultural acculturation, mindfulness, openness, tolerance, empathy, interdependence, and inter-ethnic marriage.